Diversity and Distribution of Uncultured and Cultured Gaiellales and Rubrobacterales in South China Sea Sediments - Chen, Rou-Wen; He, Yuan-Qiu; Cui, Lin-Qing; Li, Cun; Shi, Song-Biao; Long, Li-Juan; Tian, Xin-Peng (Frontiers in Microbiology, 2021)
Actinobacteria are ubiquitous in marine ecosystems, and they are regarded as an important, underexplored potential pharmaceutical resource. The orders Gaiellales and Rubrobacterales are deep taxonomic lineages of the phylum Actinobacteria; both are represented by a single genus and contain only a few species. Although they have been detected frequently by high throughput sequencing, their functions and characteristics in marine habitats remain unknown due to the lack of indigenous phenotypes. Here, we investigated the status of the orders in South China Sea (SCS) sediments using culture-independent and culture-dependent methods. Gaiellales was the second-most abundant order of Actinobacteria and was widely distributed in SCS sediments at water depths of 42 to 4280 meters, and four novel marine representatives in this group were successfully cultured. Rubrobacterales was present at low abundance in energy-limited marine habitats. An isolation strategy for Rubrobacterales from marine samples was proposed, and a total of 138 mesophilic Rubrobacterales strains were isolated under conditions of light and culture time combined with high-salinity or low-nutrient media. Marine representatives recovered in this study formed branches with a complex evolutionary history in the phylogenetic tree. Overall, the data indicate that both Gaiellales and Rubrobacterales can adapt to and survive in extreme deep-sea environments. This study lays the groundwork for further analysis of the distribution and diversity of the orders Gaiellales and Rubrobacterales in the ocean and provides a specific culture strategy for each group. The results open a window for further research on the ecological roles of the two orders in marine ecosystems.